Peternak Ayam Ras Petelur - Muhammad Nur; Mustam Mustam; Yudhi Dwi Hartono; Ahmad Muhlis Nuryadi (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2021)
Small and Medium Enterprises (SMEs) are one of the economic strength pillars of the community because their management involves the community directly, both in providing production facilities, labors, and its marketing chain. However, some SMEs failed in the middle of their business road or are unable to develop. This condition also occurs in SME of Al-Barkah Laying HenFarm. The purpose of implementing this program is to increase business capacity both from the production and management aspects of the Al-Barkah layer chicken business. The method used in overcoming these problems and achieving goals is by providing direct training, guidance, and application of science and technology. All activities were carried out jointly by the owners and employees of UKM Partners, guided by the implementation team. After implementing the program, the SME partner now: (1) understands and can conduct business planning; (2) can carry out business effectiveness and efficiency; (3) can increase understanding of the importance of order in the livestock business process; (4) Understands the importance of hygiene and cage sanitation; and (5) can increase the chicken health, egg production, and farmer income. The conclusion from the program implementation is that the Al-Barkah layer chicken business has increased production by 15% and an increase in business efficiency by 12% as a result of improvements in production and business management aspects.